Impact of plate shape on the conservation of food praxis in institutionalised elderly adults with severe Alzheimer's disease or mixed dementia: Praxalim an observational before-after non-randomized study. (November 2020) - Delaide, Valérie; Beloni, Pascale; Labrunie, Anaïs; Marin, Benoît
Abstract: Purpose: To investigate whether the shape of the food plate could affect the conservation of praxis in institutionalised elderly adults with severe Alzheimer's disease or mixed dementia. Patients and methods: We conducted a monocentric, prospective, observational, before-after case-only study in 32 patients with a loss of the ability to self-feed. The primary objective was to assess the change of food praxis using the Blandford scale at 3 weeks after changing the food plate. Secondary variables included the impact of the change of diet on the food praxis at 6 weeks, the patient's autonomy in the food intake evaluated by Tully's Eating Behaviour Scale (EBS), and the enjoyment of eating assessed by Part D of the Alzheimer's Disease-Related Quality of Life (ADRQL) scale at 3 and 6 weeks. Results: At 3 weeks after changing the food plate we observed a significant decrease in the number of aversive feeding behaviours (Δ = −0.90 ± 2.23; p = 0.03) and an improved autonomy in self-feeding (Δ = 1.88 ± 3.36.23; p = 0.001). There was also an increase in the enjoyment of eating at 3 weeks (Δ = 4.07 ± 13.02), but it was not statistically significant. These results were not consolidated at the 6 week timepoint. Conclusion: A simple change in the organisation of care during meals and the use of a familiar object can positively affect the recovery of the self-feeding autonomy of patients with severe dementia.